y-intercept for x = 0.
Substitute x = 0 to the equation of the function:
![f(x)=-32(2)^{x-3}+3\\\\f(0)=-32(2)^{0-3}+3=-32(2)^{-3}+3=-32\cdot\dfrac{1}{2^3}+3=-32\cdot\dfrac{1}{8}+3\\\\=-4+3=-1\\\\Answer:\ \boxed{y-intercept=-1\to(0,\ -1)}](https://tex.z-dn.net/?f=f%28x%29%3D-32%282%29%5E%7Bx-3%7D%2B3%5C%5C%5C%5Cf%280%29%3D-32%282%29%5E%7B0-3%7D%2B3%3D-32%282%29%5E%7B-3%7D%2B3%3D-32%5Ccdot%5Cdfrac%7B1%7D%7B2%5E3%7D%2B3%3D-32%5Ccdot%5Cdfrac%7B1%7D%7B8%7D%2B3%5C%5C%5C%5C%3D-4%2B3%3D-1%5C%5C%5C%5CAnswer%3A%5C%20%5Cboxed%7By-intercept%3D-1%5Cto%280%2C%5C%20-1%29%7D)
Combining the like terms, the simplified polynomials are given as follows:
a) 4x² - 14x + 17
b) -5x² - 20x + 8
<h3>How are polynomials simplified?</h3>
Polynomials are simplified combining the like terms, that is, adding these numbers with the same variable.
Item a:
4(x - 2)(x + 1) - 5(2x - 5)
Applying the distributive property:
4(x² - x - 2) - 10x + 25
4x² - 4x - 8 - 10x + 25
Combining the like terms:
4x² - 4x - 10x - 8 + 25
4x² - 14x + 17
Item b:
-5(x + 2)² + 28
-5(x² + 4x + 4) + 28
-5x² - 20x - 20 + 28
-5x² - 20x + 8
More can be learned about the simplification of polynomials at brainly.com/question/24450834
#SPJ1
Answer: 39
Step-by-step explanation:
x(z+3)+1+3-y
plug in the values given for each variable
6(2+3)+1+3-(-5)
use pemdas to solve
6(5)+1+3+5
30+1+3+5
31+8
39
2.03
×
1.2
---------
406
+
2030
----------
6036
×
0.5
----------
3.0180 either 3.0180 is the anwser or 1.218